Recommendations for Welcoming Back Nursing Home Visitors During the COVID-19 Pandemic: Results of a Delphi Panel - Bergman, Christian; Stall, Nathan M; Haimowitz, Daniel; Aronson, Louise; Lynn, Joanne; Steinberg, Karl; Wasserman, Michael (Journal of the American Medical Directors Association, 2020)
Nursing homes became epicenters of COVID-19 in the spring of 2020. Due to the substantial case fatality rates within congregate settings, federal agencies recommended restrictions to family visits. Six months into the COVID-19 pandemic, these largely remain in place. The objective of this study was to generate consensus guidance statements focusing on essential family caregivers and visitors. A modified 2-step Delphi process was used to generate consensus statements. The Delphi panel consisted of 21 US and Canadian post-acute and long-term care experts in clinical medicine, administration, and patient care advocacy. State and federal reopening statements were collected in June 2020 and the panel voted on these using a 3-point Likert scale with consensus defined as ≥80% of panel members voting "Agree." The consensus statements then informed development of the visitor guidance statements. The Delphi process yielded 77 consensus statements. Regarding visitor guidance, the panel made 5 strong recommendations: (1) maintain strong infection prevention and control precautions, (2) facilitate indoor and outdoor visits, (3) allow limited physical contact with appropriate precautions, (4) assess individual residents' care preferences and level of risk tolerance, and (5) dedicate an essential caregiver and extend the definition of compassionate care visits to include care that promotes psychosocial well-being of residents. The COVID-19 pandemic has seen substantial regulatory changes without strong consideration of the impact on residents. In the absence of timely and rigorous research, the involvement of clinicians and patient care advocates is important to help create the balance between individual resident preferences and the health of the collective. The results of this evidence-based Delphi process will help guide policy decisions as well as inform future research.